THE DAILY AS A SOURCE OF INFORMATION FOR THE CHOICE OF RESEARCH ISSUES IN HEALTH SCIENCES (Part II) - Balarezo-López, Gunther (2020)
Newspapers are a way to disseminate information quickly and at a lower cost. Health professionals could have this means as a way to publicize the results of their research so that more people can access it. In this regard, the objective was to continue with the review of articles related to health in the newspaper El Comercio, Lima, Peru. This news can serve as a starting point for professionals and students in the field of health, to carry out scientific research. Keywords: diary – healthcare professionals – health sciences – scientific research – topic choice